Improving Aquatic Biodiversity Estimates in Africa: Rotifers of Angola and Ghana - Radoslav Smolak; Patrick D. Brown; Robert N. Walsmith; Judith V. Ríos-Arana; Peter Sanful; Lukáš Kalous; Elizabeth J. Walsh (Diversity, 2024)
Afrotropical inland waters are highly diverse ecosystems; however, they remain poorly studied, especially for rotifers. Here, we contributed to the knowledge of the rotifer species richness in the largely understudied African countries of Angola and Ghana. We assessed the roles of habitat type and a suite of abiotic environmental factors in determining rotifer species richness of Ghana. A total of 37 sites (Ghana 32, Angola 5) in 19 water bodies from a variety of aquatic habitat types were sampled. In Ghana, we identified 118 taxa (105 species or subspecies level, 13 identified to genus). We identified 15 taxa (13 species) in the Angola samples. For Ghana, 100 of 118 (~85%) taxa were new records for the country, of which 13 species (~11%) were also new records for Africa. Nearly all the species (~93%) were new records for Angola. Species richness was positively correlated with conductivity and reservoir habitat type and negatively with pH. Redundancy analysis (RDA), conducted at the species level for the Ghana dataset, indicated suites of species associated with latitude, longitude, temperature, TDS, or pH. We also evaluated the effect of climate on species distribution in 27 African countries by conducting a review of all reports from Africa to determine factors associated with species richness. A Spearman’s correlation confirmed a significant positive correlation between the number of rotifer species and the number of climatic regions (R = 0.53, p < 0.001) for certain countries, based on species distributions in relation to Köppen–Geiger climate regions. This fact validates the environmental heterogeneity hypothesis for African rotifers. Lastly, we predicted that rotifer species richness in Ghana, as a country with a tropical climate, could approach ~190 taxa, while in climatically heterogeneous Angola we predict ~200 taxa. This study contributes to our knowledge of rotifer biogeography and species richness patterns in Africa.